Limitations of MIC as sole metric of pharmacodynamic response across the range of antimicrobial susceptibilities within a single bacterial species - Wen, X. S.; Gehring, Ronette; Stallbaumer, A.; Riviere, Jim E.; Volkova, Victoriya V. (My University, 2016)
The minimum inhibitory concentration (MIC) of an antimicrobial drug for a bacterial pathogen is used as a measure of the bacterial susceptibility to the drug. However, relationships between the antimicrobial concentration, bacterial susceptibility, and the pharmacodynamic (PD) inhibitory effect on the bacterial population are more complex. The relationships can be captured by multi-parameter models such as the E-max model. In this study, time-kill experiments were conducted with a zoonotic pathogen Pasteurella multocida and the fluoroquinolone enrofloxacin. Pasteurella multocida isolates with enrofloxacin MIC of 0.01 mu g/mL, 1.5 mu g/mL, and 2.0 mu g/mL were used. An additive inhibitory E-max model was fitted to the data on bacterial population growth inhibition at different enrofloxacin concentrations. The values of PD parameters such as maximal growth inhibition, concentration achieving a half of the maximal inhibition, and Hill coefficient that captures steepness of the relationships between the concentration and effect, varied between the isolate with low MIC and less susceptible isolates. While enrofloxacin PD against the isolate with low MIC exhibited the expected concentration-dependent characteristics, the PD against the less susceptible isolates demonstrated time-dependent characteristics. The results demonstrate that bacterial antimicrobial susceptibility may need to be described by a combination of parameters rather than a single parameter of the MIC.
Citation: Wen, X. S., Gehring, R., Stallbaumer, A., Riviere, J. E., & Volkova, V. V. (2016). Limitations of MIC as sole metric of pharmacodynamic response across the range of antimicrobial susceptibilities within a single bacterial species. Scientific Reports, 6, 8. https://doi.org/10.1038/srep37907
Keywords: Bovine Respiratory-Disease; Dosage Regimen; Pharmacokinetics; Antibiotics; Infections; Design